Использую правила: 1.
, 2.
тоже что b(x)=c(x), 3. ![log_{a} (b)+log_{a} (c)=log_{a} (bc) log_{a} (b)+log_{a} (c)=log_{a} (bc)](https://tex.z-dn.net/?f=log_%7Ba%7D%20%28b%29%2Blog_%7Ba%7D%20%28c%29%3Dlog_%7Ba%7D%20%28bc%29)
Номер 246:
4) lg(7x-x²)=1, Напишем как ![log_{10} (7x-x^{2} )=1 log_{10} (7x-x^{2} )=1](https://tex.z-dn.net/?f=log_%7B10%7D%20%287x-x%5E%7B2%7D%20%29%3D1)
Используем правило 1: ![1=log_{10}(10) 1=log_{10}(10)](https://tex.z-dn.net/?f=1%3Dlog_%7B10%7D%2810%29)
Получается: ![log_{10} (7x-x^{2} )=log_{10} (10) log_{10} (7x-x^{2} )=log_{10} (10)](https://tex.z-dn.net/?f=log_%7B10%7D%20%287x-x%5E%7B2%7D%20%29%3Dlog_%7B10%7D%20%2810%29)
Используем правило 2: 7x-x²=10
Решаем уравнение: x=2, x=5
Номер 247:
4) Переносим в правую часть: ![log_{8} (x-2)=\frac{1}{3} +log_{8} (x-3) log_{8} (x-2)=\frac{1}{3} +log_{8} (x-3)](https://tex.z-dn.net/?f=log_%7B8%7D%20%28x-2%29%3D%5Cfrac%7B1%7D%7B3%7D%20%2Blog_%7B8%7D%20%28x-3%29)
Используем правило 1: ![\frac{1}{3} =log_{8}(\sqrt[3]{8} )=log_{8}(2 ) \frac{1}{3} =log_{8}(\sqrt[3]{8} )=log_{8}(2 )](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D%20%3Dlog_%7B8%7D%28%5Csqrt%5B3%5D%7B8%7D%20%29%3Dlog_%7B8%7D%282%20%29)
Используем правило 3: ![log_{8}(x-2)=log_{8}(2(x-3) ) log_{8}(x-2)=log_{8}(2(x-3) )](https://tex.z-dn.net/?f=log_%7B8%7D%28x-2%29%3Dlog_%7B8%7D%282%28x-3%29%20%29)
Используем правило 2: x-2=2(x-3)
Решаем уравнение: x=4